Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Contents:1. The impact of corporate characteristics on the level of environmental disclosure considering the requirements of the Saudi Capital Market Authority: An applied study of Saudi energy companiesMr. Mohammed Hamoud Alshehri, Dr. Meshary Hamdan Alosaimi2. The reality of strategic management and its relationship to empowering workers in the General Administration of Education in Asir RegionMrs. Saleha Ibrahim Musa Asiri , Dr. Asia Jacob Al-Hadi Abdel-Khair3. Impact of organizational change to improve administrative performance in Ministry of housing and urban planning in Sultanate of OmanMr. Yousif Khamis Al-Kharusi , Dr. Issa Khamis Al-Kharusi , Dr. Zaid Khamis Al-Kharusi , Dr. Sultan Khamis Al-Kharusi4. The impact of investing social security funds on the sustainability of insurance funds (A study of the experiences of some Arab countries from 2013-2022)Mrs. Sanaa Taysir Al-Sharafi5. The role of management information systems on the organizational culture of employees   A case study of Faisal Islamic Bank of SudanDr. Sara Suliman Alawad Mudwi , Dr. Reda Abdelfattah Ibrahim Mohamed6. The Effect of Board of Directors’ Characteristics on the Financial Performance of Saudi Industrial Corporations: An Empirical StudyCo-Prof. Maha Faisal Alsayegh, Mrs. Fatmah Mohammad Baaqeel7. Evaluation of commitment to applying risk management in the events and conferences sector  in the Riyadh region, KSAMrs. Lulu Saud Alshubaili
Keywords: Journal of Economic, Administrative and Legal Sciences